Exploring the Role of SULT1E1- A Metabolic Gatekeeper or Risk Factor for Diseases - Sonika Ghanghas,; Krishna Dahiya,; Pooja Suneja,; Amita Suneja Dang, (The Bioscan, 2026)
Endocrine-disrupting chemicals (EDCs), such as bisphenol A (BPA), pose a significant threat to human health by interfering with hormonal homeostasis. This review posits that the cytosolic sulfotransferase enzyme SULT1E1—a critical gatekeeper for inactivating both endogenous estrogens and exogenous xenoestrogens via sulfation—serves as a central mechanistic node linking environmental EDC exposure to the pathogenesis of reproductive and metabolic disorders. We synthesize evidence demonstrating that BPA, a ubiquitous EDC, disrupts endocrine function not only by mimicking estrogen but also by directly inhibiting SULT1E1 activity. This inhibition leads to a state of functional hyperestrogenemia, which provides a plausible explanatory model for the comorbid development of conditions such as polycystic ovary syndrome (PCOS), infertility, and hormone-sensitive cancers (e.g., breast and endometrial cancer). Furthermore, SULT1E1 dysfunction extends to systemic metabolism, contributing to insulin resistance and thyroid hormone disruption. The review critically evaluates the diagnostic and therapeutic potential of targeting the SULT1E1 pathway, including strategies to restore its protective sulfation function. We conclude that the impairment of SULT1E1 by EDCs like BPA represents a unifying biological mechanism connecting pervasive environmental chemical exposure to the rising burden of chronic non-communicable diseases, underscoring an urgent need for both enhanced regulatory policies and targeted biomedical interventions. Keywords SULT1E1, Bisphenol A (BPA), Endocrine disruption, Hyperestrogenemia, Metabolic-reproductive comorbidity